Efficiency and competitiveness of banking in Indonesia based on bank core capital group - Sylvia Arief Ischak; Mohammad Syamsul Maarif; Irman Hermadi; Zenal Asikin (Economies, 2024)
The banking sector in Indonesia is currently growing and developing. This is due to the Indonesian Financial Services Authority (OJK) implementing reforms to strengthen the banking sector and enhance financial stability. One of the reforms is in the form of regulation that categorizes banks into four special categories based on core capital. This study aimed to analyzing the relationship between the efficiency and competitiveness of BUKU 1 to IV banks and KBMI 1 to IV banks in Indonesia. The data in this study were collected from journals, scientific articles, banking statistics, and financial reports of all banks based on KBMI (formerly BUKU) published by the Financial Services Authority (OJK) and the Indonesia Stock Exchange (IDX) for the period from 2018 to 2023. The results found there are no significant changes in patterns within the BUKU and KBMI groups. However, in the KBMI 4 group, a positive correlation between competitiveness and efficiency is observed, meaning that an increase in efficiency will be followed by an increase in a bank's competitiveness. This group has the same pattern as the KBMI 1 and KBMI 3 groups. Meanwhile, the KBMI 2 group still follows the same pattern as in the BUKU 2 group, where an increase in efficiency is accompanied by a decrease in competitiveness, and vice versa; an increase in competitiveness will be followed by a decrease in a bank's efficiency.
Keywords: 330; banking; competitiveness; efficiency; core capital; concentration ratio